The Concept of Peace in the Qur’an: A Socio-Thematic Analysis of Muslims’ Contestation in Salatiga, Indonesia - Adang Kuswaya (P3M STAIN Kudus, 2021)
This research aims not only to understand the concept of peace in the Qur’an but also analyze Muslims’ contestation in Salatiga to lead to a peaceful life among religious believers. It requires an in-depth examination on dialectical perspectives between the ideal concept of peace in the Quran and the reality of a peaceful culture in the public sphere. Methodologically, this research combines literature review and semi-structured interviews to gather theoretical data based on social responses and literature of contemporary Qur’anic interpretation. The research subjects consist of (1) Muslims living with non-Muslim family members in the same house, (2) Muslims in a non-Muslim neighborhood, (3) religious figures, and (4) non-Muslims with Muslim family members. In order to interpret a special meaning of Qur’anic terms related to peaceful life, this research employs a hermeneutical approach of socio-thematic interpretation of the Qur’an. In conclusion, this research points out that Muslims in Salatiga play a significant role in building a peaceful life where some concepts, such as unity, freedom, honesty, and respect, are principles thriving vividly throughout society. Additionally, tolerance is a foundation of social interaction leading them to cooperate. Besides, several values, namely harmonization, tolerance, and coexistence, can be seen as dominant ideas within the communities, and practices such as cooperation and friendship can also be seen in their daily life. Thus, this research affirms that the Muslim majority can lead to tolerance and accommodate diversity as a way of life.